A dinâmica dos sistemas litorais do Sul de Moçambique durante os últimos 30 anos - Moreira, Maria Eugénia (Finisterra, 2005)
Erosion is the dominant process of Mozambique’s coastal dynamics. In more than 90% of the coastline, it is a natural process that occurs as a consequence of tropical cyclones and of the recent relative sea level rise. The consequences of these processes are the retreat of the coastline and the occurrence of transgressive phenomena in all the sandy systems (beach-dune-lagoon). These are due to the erosion of the upper- and meso-tidal forms, such as beaches, dunes, spits, barrier islands and cliff fronts. At the same time, an infilling of the low coastal forms occurs that is due to the submergence of the sub- and meso-tidal forms, such as beachrock platforms (bio-erosion pools and solution benches filled with sand), estuarine bars and mudflats. Wherever the beachrock platforms are wide enough, despite being partially submerged, they preserve the erosion of the connected beachdune system. The salinization of the freshwater coastal aquifers, both in islands and in the mainland, and the growth of the coral reefs are two other consequences of this gradual submergence. The retreat values recorded in the beaches that experienced these natural dynamics in the southern coast of Mozambique range from 0.11 to 1.10 m/year over the last 31 years (1973-2004). However, the maximum erosion values of 0.95 and 1.75 m/y took place in the southern border beach-dune system (Ponta do Ouro), and were due to disorderly exploitation by the tourist industry. The inland migration of the spit-dune system over the mangrove platforms has changed the sedimentation pattern, and the sand now overlaps the silt mudflats. For this reason, the mangrove flora has undergone ecological changes, such as the substitution of helophyte (Rhyzophora and Ceriops ssp.) by psammophyte species (Aviccenia marina).